Co-pyrolysis of swine manure and pinewood sawdust: Evidence of cross-interaction of the volatiles and profound impacts on product characteristics. (December 2021) - Li, Qingyin; Lin, Haisheng; Fan, Huailin; Zhang, Shu; Yuan, Xiangzhou; Wang, Yi; Xiang, Jun; Hu, Song; Bkangmo Kontchouo, Félix Mérimé; Hu, Xun
Abstract: Co-pyrolysis of feedstock with varied compositions is a common practice, during which cross-interaction of volatiles from single feedstock requires particular attentions as it may affect the product properties. In this study, co-pyrolysis of swine manure and pinewood sawdust was conducted. The results proved the interaction of volatiles from pyrolysis of swine manure with pinewood sawdust and their significant impact on the evolution of pyrolysis products. The interaction effect favored the formation of bio-oil and biochar but diminished the production of gases, as the cross-interaction transformed the gaseous precursors into heavier organics. Although cross-interaction facilitated the formation of organics with π-conjugated structures, The Fourier transform ion cyclotron resonance-mass spectrometry (FT-ICR MS) characterization showed that the chemical species with large carbon number in the sawdust-derived bio-oil were transferred into the carbonaceous substance. The bio-oil from co-pyrolysis was thus lighter, and the interaction effect also inhibited the generation of nitrogenous species. The cross-interaction of volatiles made the biochar oxygen-rich and enhanced the thermal stability. Furthermore, in situ Diffuse Reflection Infrared Fourier Transform Spectra (DRIFTS) results indicated that the interaction of volatiles resulted in the formation of more functionalities like –OH, -C-H and CO on the biochar. Graphical abstract: Image 1